Comparison of Retroperitoneoscopic Versus Transperitoneoscopic Resection of Retroperitoneal Paraganglioma: A Control Study of 74 Cases at a Single Institution. Issue 7 (February 2015) - Xu, Weifeng; Li, Hanzhong; Ji, Zhigang; Yan, Weigang; Zhang, Yushi; Xiao, He; Zhang, Xuebin; Liu, Guanghua
Abstract : Abstract: We aimed to compare the safety and patient outcomes of retroperitoneal paraganglioma (PG) following the retroperitoneoscopic and transperitoneoscopic approaches based on large samples. Seventy-four patients with retroperitoneal PG undergoing laparoscopic resection from June 2004 to September 2013 were retrospectively included. The patients were divided into the retroperitoneal (n = 40) and transperitoneal (n = 34) groups. Demographic and perioperative data, including the operation time, estimated blood loss, incidence of intraoperative hypertension, bowel recovery day, postoperative hospital stay, and systemic inflammatory response syndrome (SIRS) were recorded. The retroperitoneal group showed a shorter operation time and earlier postoperative exsufflation time compared with the transperitoneal group (84 ± 28.5 minutes vs 115 ± 35.7 minutes and 1.7 ± 0.6 vs 2.3 ± 0.7 day, respectively; both P < 0.001). No significant differences in the baseline data were observed between 2 groups. All patients, except for 1 case of open conversion, underwent laparoscopic surgery. There were no patient deaths. Data analysis demonstrated no significant difference in the surgical blood loss, incidence of surgical blood pressure elevation, postoperative hospital stay, or incidence of SIRS between 2 groups. The operation time for the retroperitoneoscopic resection of retroperitoneal PG is shorter, and gastrointestinal functions improve more quickly compared to the transperitoneoscopic approach. This study may provide a valuable source of clinical information for clinicians in related fields.